Presentation of the CONCISE project - Warwas, Izabela; Dzimińska, Małgorzata; Krzewińska, Aneta (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
In this chapter, the author presents the project “CONCISE: Communication role on perception and beliefs of EU Citizens about Science”, describing the countries, institutions and organisations participating in the project, its main assumptions, aims and research questions. Readers are familiar with the scheme of the entire study, which consisted of desk research, in-depth interviews, workshops, and public consultations carried out in five European Union countries. It should be emphasised that the project partners developed a common methodology, based on participatory research, while at the same time leaving a certain amount of freedom, thanks to which they could adapt the research procedure to the specific cultural conditions of each country. In this chapter, you will also find information about the collected research material and the methods of processing it, using various computer programs that allow for the analysis of the language layer (TLab), quantitative data (SPSS) and qualitative data (NVivo).